Metodología Montessori y la motricidad fina en los niños del nivel inicial II de la Escuela de Educación Básica Mons. Juan María Riofrío, de la ciudad de Loja, en el periodo 2021-2022. - Medina Cango, Erika Geraldine (2022)
2.1. Abstract Summary Fine motor skills are an important part of a child's development, encompassing skills of precision, concentration, coordination and control of both hand and eye movements, which in turn facilitates the acquisition of writing. The objective of this work was to determine how the María Montessori methodology strengthens fine motor skills in children of the initial level II of the Mons. Juan María Riofrío Basic Education School in the city of Loja in the period 2021-2022. It was developed under the quasi-experimental design by manipulating the independent variable, it also had a mixed approach that allowed analyzing and collecting data both qualitatively and quantitatively, the scope was descriptive, contributing to obtain information on the variables; the methods used were the inductive-deductive used in the formulation of the theoretical framework; the analytical facilitated studying the aspects of each variable separately; and, the synthetic allowed to investigate the effectiveness of the Montessori methodology. As an instrument, an appraisal scale adapted from the initial education curriculum was applied, which showed that 100% of children were at the initiation level and in process, but after applying the activity guide, 56% of those investigated managed to be in the acquired level. Concluding that the Montessori methodology helps in the development of fine motor skills, considering that the materials proposed within it are adaptable for any age, subject or ability, within the areas of language, mathematics and gross motor skills among others. Keywords: Bimanual, coordination, Montessori, precision, digital clamp, manual